Structure design study of vacuum magnetic fluid seal - Liu, Sijia; Li, Decai; He, Xinzhi; Zhang, Zhili (Frontiers in Materials, 2022)
Aiming at the requirement of high vacuum and leakage rate of a small diameter low speed device of an enterprise, four kinds of vacuum magnetic fluid sealing device structures are proposed and their advantages and disadvantages are analyzed, and a double magnets multi-stage magnetic fluid sealing device is specifically designed to meet the use requirements. The ANSYS simulation software is used to analyze and calculate the magnetic field strength and distribution of the magnetic fluid seal device, discuss the influence of the number of intermediate section pole teeth and the seal gap size on the pressure resistance of the magnetic fluid seal and summarize the law. Within the allowed space, the design and processing of more teeth in the intermediate shaft section is conducive to improving the pressure resistance of the device, generally not more than 20 teeth; under the condition that other parameters remain unchanged, the pressure resistance decreases as the seal gap increases. Based on the simulation analysis, the optimized structure of the magnetic fluid sealing device is determined to improve the sealing capacity of the device, and the results show that the structural design of the device is reasonable and meets the working requirements.